Copépodos (Crustacea) de aguas superficiales del Mar Caribe Mexicano (mayo, 1991) - Suárez-Morales, E (Universidad de Costa Rica, 1997)
Zooplankton samples (May, 1991) from neritic and oceanic waters off the eastern coast of the Yucatan Peninsula, produced 70 species of pelagic copepods, Undinula vulgaris, Farranula gracilis, Calanus minor and Temora turbinata were dominant (more than 60% of individuals). Mean diversity was moderate (2.48 bits/ind.). Clustering with the Bray Curtis Index suggests absence of a definite gradient in the local copepod community; coastal species were recorded well inside the oceanic zone and vice versa. This may result from mixing of coastal and shelf water with oceanic water because of (1) the narrowness of the platform and (2) the effect of the local mesoscale circulation pattems